Real-world efficiency of pharmacogenetic screening for carbamazepine-induced severe cutaneous adverse reactions. - Zhibin Chen (Public Library of Science (PLoS), 2014)
Objectives We evaluated the cost and efficiency of routine HLA-B*15 ∶ 02 screening to prevent carbamazepine-induced Stevens-Johnson syndrome and toxic epidermal necrolysis (CBZ-SJS/TEN) in Hong Kong. Methods Data were extracted from patients who commenced CBZ as the first-ever AED treatment or tested for HLA-B*15 ∶ 02 allele in three years before policy implementation (pre-policy: 16 September 2005 to 15 September 2008) and three years after (post-policy: 16 September 2008 to 15 September 2011). Using published unit costs, we estimated the cost of screening by comparing the costs to prevent and treat CBZ-SJS/TEN. We compared the number of person-tests needed and the cost to prevent resultant death with cancer screening programs. Results The number of screening tests needed to prevent one case of CBZ-SJS/TEN was 442, and to prevent one resultant death was 1,474 to 8,840. The screening cost was $332 per person, of which 42% was attributed to an additional consultation to review result and prescribe appropriate medication. HLA-B*15 ∶ 02 screening expended $146,749 to prevent a case of CBZ-SJS/TEN, and $489,386- $2,934,986 to prevent a resultant death. The corresponding numbers of tests and costs for mammography and Pap smear to prevent death due to breast and cervical cancers were 7,150 and 7,000, and $614,900 and $273,000, respectively. Comparing to the SJS/TEN treatment cost, HLA-B*15 ∶ 02 screening would become cost saving if a point-of-care test of less than $37 was available. Conclusions HLA-B*15 ∶ 02 screening is as efficient as mammography and Pap smear in preventing death. Development of point-of-care testing will vastly improve efficiency.